Prediking uit die Ou Testament - J. Janse van Rensburg (Acta Theologica)
Preaching from the Old Testament has many pitfalls. Besides the danger of moralism, allegory and typology, there is the problem of preaching Christ from the Old Testament. Forcing Christ into Old Testament texts has Old Testament scholars up in arms, to the extent that some believe that Christ is not found in the Old Testament and that there are no Messianic texts. Between reading Christ into the Old Testament and not preaching Christ from the Old Testament, the preacher must find a responsible way of dealing with the many challenges. The article endeavours to provide some guidelines and principles for preaching from the Old Testament to a Christian congregation.